TINGKAT KEPUASAN PASIEN BPJS DI PUSKESMAS MELATI KECAMATAN PERBAUNGAN KAB. SERDANG BEDAGAI - ILHAMDY RAMADHAN; MUHAMMAD KHADAFI (JURNAL ILMIAH SIMANTEK, 2020)
As a health care provider of Jaminan Kesehatan Nasional (JKN), puskesmas have to provide the best health care forcommunity. Health care service satisfaction assessment can be measured by knowing the level of community satisfactionwith the health care service. To find out how is the satisfaction level of BPJS patients of puskesmas melati. The studyapplied observational analysis with cross sectional design and accidental sampling. Based on the research results obtainedNRR from each indicator of service procedures (3,412), service requirements (3,422), the explicit of service personnel(3,331), officer responsibility (3,423), service personnel ability (3,522), service speed (3,166), justice received service(3,522), courtesy and friendliness of staff (3,700), fairness of service costs (3,978), certainty of service costs (3,944),environmental comfort (3,244), environmental security (3,367), discipline of service personnel (3,400), certainty of serviceschedules (3,444 ). Service quality and satisfaction levels are very good. However, there are 5 of 14 indicators that still getthe lowest score, namely, service speed, environmental comfort, clarity of staff, environmental security and serviceprocedures that have the lowest NRR.